The Effectiveness of HIIT Exercise on Aerobic Energy System Adaptation in Athletes: A Literature Review - Zaniar Dwi Prihatin Ciptadi; Irvan Septianto; Fadel muhammad; Arfan Julistya Hadi; Fini May Putriani (Jurnal Ilmu Keolahragaan, 2025)
High-Intensity Interval Training (HIIT) is an effective training method for enhancing athletic performance through physiological adaptations in the body’s energy systems. This literature review aims to analyze the effectiveness of HIIT in promoting aerobic energy system adaptations in athletes based on current scientific evidence. Articles were retrieved from the Scopus, DOAJ, and Google Scholar databases using the keywords “High-Intensity Interval Training,” “HIIT,” “aerobic,” “VO₂max,” “energy system adaptation,” and “athlete,” covering publications from 2020–2025. Based on inclusion and exclusion criteria, five articles were analyzed in depth using the annotated bibliography method. The findings indicate that HIIT consistently improves VO₂max, aerobic capacity, energy metabolism efficiency, and athletes’ cardiovascular endurance. HIIT protocols with an intensity of 80–95% HRmax and training duration of 3–8 weeks have been shown to effectively produce significant physiological adaptations. Moreover, adjusting work–rest intervals according to the characteristics of each sport has a positive impact on competitive performance enhancement. This review confirms that HIIT is an efficient and evidence-based training strategy for improving athletes’ aerobic capacity. However, further large-scale experimental research is needed to strengthen the generalization of these findings.